Separating the Measurement and Evaluation of Intellectual Capital Elements with Evaluator Functions - János Kövesi; Tamás Jónás; Zsuzsanna Eszter Tóth (Theory, Methodology, Practice, 2010)
The purpose of this study is to contribute to the use of evaluator and utility functions in order to increase the reliability of scorecard based intellectual capital measurement methods and to express and aggregate the utility of IC elements to the organization. The conducted field experiment integrates the results of interviews with 23 brand name customers through examining the customer satisfaction measuring practice of service provider companies. The main finding is that the adequately calibrated evaluator functions assign perceived customer satisfaction to its scorecard based measured values and mitigate the distortions of scorecard based measurements. The evaluator function interpreted as a kind of utility function reflects the utility of IC values derived from a scorecard based measurement method. Our research discusses the repertoire of aggregating the utility of IC elements as well.